Unlocking the power of Mentimeter: Exploring EFL students' perspectives for enhancing writing proficiency - Syabilla, Zalsa Febrina; Heriyawati, Dwi Fita; Romadhon, Muhammad Galuh Elga; Aprilia, Putri Kurniawan (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2023)
This study investigates the perceptions of EFL students' perceptions regarding the Mentimeter-based activities andtheir specific features for help learning writing skills. The quantitative research method through descriptive analysis was employed, involving 30 EFL students from a private middle school in Malang. A closed-ended questionnaire was given via Google Forms to gather data. The results indicate that students perceive Mentimeter as a valuable tool for enhancing their learning experiences, promoting creativity, and providing a fun and interactive learning environment in writing skill. Mentimeter is also useful in promoting vocabulary expansion, language mechanics development, and comprehension. It was noted that the Word Cloud was particularly helpful for testing students' writing skills, engaging them in class, and improving academic outcomes. It may encourage competency growth, feedback, and discussions. By shedding light on Mentimeter's potential as a tool to help learning writing abilities for EFL students', the study adds to the body of knowledge on cutting-edge language learning techniques.